PEMBUATAN DAN PENGUJIAN SKATEBOARD ELECTRIC - Edison, Edison (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2020)
The main objective of this research is to know how to make and test Electric Skateboard properly. limitation of the issues to be discussed are the Making of Electric Skateboard, the making of a skateboard using strong maple wood and impact resistance, the use of this tool is only used for games, the use of this tool is only used on a level road, the use of this tool cannot be used for freestyle. Electric Skateboard testing is conducted to determine the distance traveled by electric skateboards in 10 m with a load of 51 kg with a time of 15.22 seconds, this electric skateboard driving motor with a capacity of 12volt150 watts with a motor speed of 1450 Rpm. With a 12volt 7.2ampere battery power source. distance and time taken with a load of 51 kg with a distance of 3.2 km with 1 hour, 24 minutes until the battery runs out while no load with the distance and time taken is 34,671 km with a time of 9 hours 37 minutes with the battery running out.